Atrioventricular Conduction Delay in the Second Trimester Measured by Fetal Magnetocardiography - Annette Wacker-Gussmann; Henrike Paulsen; Krunoslav Stingl; Johanna Braendle; Rangmar Goelz; Joerg Henes (Journal of Immunology Research)
Introduction. Fetal AV block in SSA/Ro pregnancies is generally not seen before 18-week gestation and onset is rare after 28-week gestation. If complete AV block appears, it is believed to be irreversible. The purpose of the study was to evaluate precise electrophysiological AV conduction from 18-week gestation onwards. Patients and Methods. 21 fetuses of pregnant women with collagen vascular diseases were included in the study group and 59 healthy fetuses served as controls. In addition to fetal echocardiography, fetal magnetocardiography (fMCG) was used to investigate precise electrophysiological fetal cardiac time intervals (fCTIs). Results. The PR segment (isoelectric segment between the end of the P wave and the start of the QRS complex) was significantly prolonged (P<0.036 2nd trimester, P<0.023 3rd trimester) in both trimesters within the study group. In fetuses less than 23-week gestational age, a nearly complete separation was found, where a PR segment of 60 ms or greater completely excluded control fetuses. All other fCTIs did not differ significantly. None of the fetuses progressed to a more advanced heart block. Conclusion. Slight antibody effects in pregnancy, leading to PR segment prolongation, can already be seen from 18-week gestation onwards by fMCG. Serial fetal Doppler echocardiography and additional fMCG can be useful methods to measure early and precise AV conduction time, to achieve best surveillance for these high-risk pregnancies.